Possibilities of interpretation theory in the study of contemporary choral works - Pallas, Roman (Aura musica, 2012)
Practicing and performing of complicated contemporary choral pieces can be easier with the use of a theory of interpretation. As a theoretical basis we can use the Jaroslav Zich's theory, which have to be partly modified to be useful for contemporary music. A theoretical knowledge are necessary part of a conductor's education as it's use can bring required perspective, easier orientation and prioritization in a seemingly confusing score.
Keywords: theory of interpretation; contemporary music; choir; conductor